The Influence Of Financial And Non-Financial Information To Underpricing Of Stock Prices In Companies That Conduct Initial Public Offering - Yuliani, Yuliani; Wahyuni, Dwi; Bakar, Samadi W (Ekspektra : Jurnal Bisnis dan Manajemen, 2019)
Underpricing is a condition which shows that stocks price at primary market is lower than the stocks price at secondary market. This research was aimed to find out the influence of financial and non-financial information in the form of Debt to Equity Ratio (DER), Return on Equity (ROE), underwriter reputation, and the percentage of stocks offering to underpricing of stock prices in companies that conducted Initial Public Offering (IPO). The population in this research were the companies that conduct IPO listed in the Indonesian Stock Exchange in the period time of 2013-2017. The sampling technique was purposive sampling method and there were obtained 52 companies as the samples. The used data were the secondary data in the form of the data of companies that carry out IPO and listed in IDX in 2013-2017and the prospectus of the companies.The data analysis technique was multiple linier regression. The result of this reseach showed that Return on Equity (ROE) and Underwriter Reputation has a negative significant effect to underpricing, while Debt to Equity Ratio (DER) and Percentage of Stocks Offering doesn’t have significant effect to underpricing.